Amniotic Fluid Index and its Impact on Mode of Delivery and Fetomaternal Outcome in Term PROM - Khan, Sadia; Shetu, Shain Fariya; Chowdhury, Mushrefa; Sarker, Afsana (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Background: The increasing prevalence of term premature rupture of membranes (PROM) poses significant challenges to obstetrical management, necessitating enhanced predictive methodologies for optimal clinical outcomes. Objectives: Primary Objective: To evaluate the association between amniotic fluid index (AFI) and mode of delivery, as well as fetomaternal outcomes, in pregnant women at term with PROM. Specific Objectives: To assess the association between AFI values at admission and the mode of delivery (vaginal vs. cesarean) in Term PROM cases. To determine whether low AFI (AFI < 5 cm) is a predictive marker for induction failure and higher cesarean delivery rates. To explore potential indications for cesarean delivery in relation to AFI status, including fetal distress and failed induction. Materials and Methods: This analytical cross-sectional study was conducted at Dhaka Medical College, Bangladesh, from August 2019 to February 2020. A total of 126 pregnant women with confirmed term PROM (37–40 weeks) were enrolled. Inclusion criteria were singleton cephalic pregnancies with adequate pelvis; exclusions included preterm PROM, previous uterine surgery, non-cephalic presentation, intrauterine growth restriction (IUGR), and maternal hypertensive or diabetic disorders. AFI was measured by ultrasound and patients were grouped as Group A (AFI e” 5 cm) and Group B (AFI < 5 cm). After PROM confirmation, patients were monitored for spontaneous labor for 24 hours; if labor did not begin, induction was performed based on cervical status. Outcomes included mode of delivery and fetomaternal complications. Data were analyzed using SPSS version 22 with chi-square tests for categorical variables; p < 0.05 was considered significant. Results: Among 126 term PROM cases, 76 had AFI e” 5 cm (Group A) and 50 had AFI < 5 cm (Group B). Vaginal delivery occurred in 50 women in Group A (65.8%), of which 26 had spontaneous onset of labor and 14 required induction. In Group B, only 5 women (10%) delivered vaginally, with 1 spontaneous and 4 induced labors. Cesarean section rates were significantly higher in Group B (90.0%) compared to Group A (34.2%) (p = 0.002), primarily due to fetal distress and failed induction. Induction outcomes showed that successful vaginal delivery after induction was 77.8% in Group A versus 25% in Group B (p = 0.003). Neonates in Group B had increased need for resuscitation (38.0% vs. 10.5%, p = 0.02) and higher rates of complications including pneumonia, respiratory distress syndrome, neonatal sepsis, hypoglycemia, and other complications. The proportion of neonates without complications was significantly lower in Group B (34.0%) compared to Group A (71.1%) (p = 0.01). Bangladesh J Obstet Gynaecol, 2025; Vol. 40(1): 13-18